Teaching of mother tongue: difficulties and formative needs as stated by Elementary School teachers - Videira Parisotto, Ana Luzia [UNESP]; Rinaldi, Renata Portela [UNESP] (Editora Univ Federal Parana, Centro Politecnico, 2016)
Schoolteachers face many challenges in the teaching of mother tongue from the viewpoint of the ability to read and write and literacy as social practices. With regard to the city of Presidente Prudente, Brazil, it is vital to understand how the continued education process occurs in the practice of Elementary School teachers in order to be able to devise new formative strategies - at both the municipal and school levels - aimed at improving the teaching of mother tongue. To that end, this study aims to reflect on the education of teachers of the first years of Elementary School based on their difficulties and formative needs vis-a-vis the teaching of mother tongue. This qualitative research - funded by CNPq (National Council for Scientific and Technological Development) - analyzes data collected by means of a questionnaire responded by teachers from 22 schools under the Municipal Department of Education. In order to limit the scope of the investigation, this study focuses on the participating teachers' answers to two of the questions on the questionnaire - one about difficulties they find in the teaching of mother tongue and another on their educational needs. Results indicate that the main difficulties identified by participants regarding the teaching of mother tongue are in line with their stated formative needs.
Keywords: teaching of mother tongue; teachers' education; formative needs